Effect of torrefaction on thermal degradation and functional group of oil palm solid waste - Chang, Siaw Sang; Sambeth, Sharwin Kumar; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (Elsevier Ltd, 2022)
This study investigated the influence of the torrefaction process on thermal degradation and chemical changes of oil palm solid waste (OPSW) through thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) analysis. Palm kernel shell (PKS) showed the highest mass and energy yield after the torrefaction process. Furthermore, torrefied PKS (TPKS) showed the highest heating value (23.10 MJ/kg). Weight loss in active pyrolysis stages was reduced after the torrefaction, thus indicates the lignocellulosic component decomposition. OPSW showed a reduction in hydroxyl group (−OH) after torrefaction resulting in hydrophobicity characteristic. Torrefaction has significantly enhanced the characteristics of OPSW as solid biofuel.